Rethinking Economic Conditions and Environmental Attitudes: Macroeconomic Effects, Individual Experiences, and Subjectivity. (August 2017) - Mayer, Adam; Smith, E. Keith
The global environmental concern literature has focused on economic development as a contextual predictor of environmental attitudes with conflicting empirical results. Some studies, informed by postmaterialist theory or the affluence hypothesis, find that national affluence increases environmental concern, whereas others find the opposite. In this article, we qualify the economy and environmental attitude relationship by arguing that it has several dimensions: long-term macroeconomic history, short-term economic growth, individuals' recent economic experiences, individuals' subjective understandings of the national economy, and their personal economic circumstances. This holistic framework is operationalized with multilevel models and data from the Life in Transition II project, using outcomes for climate change attitudes. We find that recent economic hardships at the individual level (e.g., a job loss) have a positive to null effect. More subjectively, respondents who believe that the recent global recession had a negative effect on their household are more concerned with climate change. At the country level, long-run economic development does little to explain cross-national differences in climate change attitudes whereas short-run, relative economic growth increases both climate change concern and willingness to pay for climate policy. More broadly, future research should de-emphasize long-run, macroeconomic conditions as determinants of environmental attitudes.